Fostering Readiness of Future Doctors and Nurses for Teamwork - I. V. Ostrovslaya; N. G. Sheina (Здоровье мегаполиса, 2024)
Background. “Teamwork and leadership” is a core universal competency established by the Federal State Educational Standards of the Russian Federation. All students in any higher education program (specialist’s, bachelor's, master's, and other degrees) should acquire this competency before graduation since teamwork is a leading way to carry out joint activities. Therefore, it is crucial to study the development of teamwork skills among yesterday's students and future specialists with higher medical education.Materials and methods. The authors analyzed the models of team development and the indicators of acquiring teamwork and leadership skills among future nurses and doctors. As a result, six components of effective team development in a medical organization were identified: support from leaders, team synergy, mutual understanding and confidence in team members, mutual assistance and support, consensus in goals and intentions, delineation of responsibilities, and assignment of roles. These components laid the foundation for the team development model in a medical organization.Findings. The empirical study involved future doctors and nurses as well as practicing medical staff (n = 472). It was found that the processes for fostering the readiness of future doctors and nurses for teamwork were generally at a satisfactory level. Meanwhile, 56.9% of future doctors and almost half of future nurses could not unequivocally answer the question about classes for developing teamwork skills. Respondents are likely to acquire teamwork skills both in and out of the classroom.Discussion. The questions “Where and when should students acquire teamwork skills?” and “Whether educational programs should include special classes dedicated to developing teamwork skills?” require additional studies.